A novel terminal structure for total dose irradiation hardened of a P-VDMOS - 唐昭焕 刘嵘侃 谭开洲 罗俊 胡刚毅 李儒章 任华平 王斌 (Journal of semiconductors, 2014)
Using positive surface charge instead of traditional γ-ray total dose irradiation, the electric field distribution of a P-channel VDMOS terminal has been analyzed. A novel terminal structure for improving the total dose irradiation hardened of P-channel VDMOS has been proposed, and the structure is simulated and demonstrated with a -150 V P-channel VDMOS. The results show that the peak current density is reduced from 5.51 × 10^3 A/cm^2 to 2.01 × 10^3 A/cm^2, and the changed value of the breakdown voltage is 2.5 V at 500 krad（Si）. Especially, using 60Co and X-ray to validate the results, which strictly match with the simulated values, there is not any added mask or process to fabricate the novel structure, of which the process is compatible with common P-channel VDMOS processes. The novel terminal structure can be widely used in total irradiation hardened P-channel VDMOS design and fabrication, which holds a great potential application in the space irradiation environment.